Students’ Perception Towards NNESTs & NESTs’ Teaching Styles: A study at State Islamic University of Ar-Raniry - Fadhlur Rahman; Ella Yuzar (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2020)
This paper aimed to investigate students' perspective towards their NESTs and NNESTs' teaching styles and students’ preferred teaching styles. The participants for this study were collected from fifty-two English Education students of State Islamic University of Ar-Raniry who had studied with both NEST and NNEST. Data were obtained from a combination of administering questionnaire and conducting two focus group interviews. The questionnaire as the research instrument was adopted from Grasha's (1996) Teaching Style Inventory. Interviews were conducted to gain more comprehensive information regarding students' perception of NEST and NNESTs’ teaching style and differences that students identified when leaning with NEST and NNEST. Using descriptive statistical analysis for the questionnaire and utilizing Miles, Huberman, and Saldaña’s (2014) approach for qualitative interview analysis, the study revealed that both NEST and NNEST were perceived to have personal model teaching style and interestingly, it is also the participant preferred style. It also presented that NESTs and NNESTs have their distinctive roles in teaching-learning that are complementary to create a successful learning environment. The current research has contributed to enrich the literature work in the discussion of how students perceive NEST and NNESTs’ teaching performance with implications for educational practitioners, stake holders and institutions.